Penerapan Arsitektur Dekonstruksi pada Perancangan Pusat Kreativitas Seni Media Baru di Pekanbaru - Muhammad Poeji Hartadinata; Yohannes Firzal; Gun Faisal (Universitas Medan Area, 2022)
Culture movement in society has a linear relationship with the development of the art. To face the demands of the times, the artists start to integrate the arts with other disciplines in the process of the creation of works of art considered to be more able to accommodate the expression and the communication is conveyed in a work of art. This is known as new media art. New media art which is the result of undue hybridisation between pure art with technology capable of growing very rapidly. This development extends to all regions in Indonesia. In Pekanbaru, new media art was getting very enthusiasm of the pop art from a variety of backgrounds and ages, but it is unfortunate development is still lacking. This problem can be seen from the lack of facilities or container that can overshadow and accommodate creativity and introduce the work of new media art. Based on these problems, it needed a container that can overshadow the pop art new media as well as introduce new media art to the community, therefore drafted a center for creativity of new media art which can facilitate the activities in the field of new media art whether in the form of the process of creation of works of new media art and activities pertujukkan Design Creativity Center New Media Art is applying the principles of the Architecture of Deconstruction which has the meaning of freedom of the rhetorical structures of composition that is formal. The freedom of form that is a representation of the way of thinking the architecture of the deconstruction that do not want to be bound from the rules that have been there to interpret the freedom of the air-creativity, innovative and always fresh in the new media art. So in the hope Center for the arts creative media this can bring out the creativity of the artist through the architectural elements dekontruktif.